Influence of the length of institutionalization on older adults' postural balance and risk of falls: a transversal study - Wagner Oliveira Batista; Edmundo de Drummond Alves Junior; Flávia Porto; Fabio Dutra Pereira; Rosimere Ferreira Santana; Jonas Lírio Gurgel (Universidade de São Paulo, 2014)
OBJECTIVE: to ascertain the influence of the length of institutionalization on older adults' balance and risk of falls.METHOD: to evaluate the risk of falls, the Berg Balance Scale and the Timed Get Up and Go test were used; and for measuring postural balance, static stabilometry was used, with acquisition of the elliptical area of 95% and mean velocities on the x and y axes of center of pressure displacement. Parametric and nonparametric measures of association and comparison (α<0.05) were used.RESULTS: there was no significant correlation between the length of institutionalization and the tests for evaluation of risk of falling, neither was there difference between groups and within subgroups, stratified by length of institutionalization and age. In the stabilometric measurements, there was a negative correlation between the parameters analyzed and the length of institutionalization, and difference between groups and within subgroups.CONCLUSION: this study's results point to the difficulty of undertaking postural control tasks, showing a leveling below the clinical tests' reference scores. In the stabilometric behavior, one should note the reduction of the parameters as the length of institutionalization increases, contradicting the assumptions. This study's results offer support for the development of a multi-professional model for intervention with the postural control and balance of older adults living in homes for the aged.